2006
DOI: 10.1073/pnas.0602030103
|View full text |Cite
|
Sign up to set email alerts
|

Arf gene loss enhances oncogenicity and limits imatinib response in mouse models of Bcr-Abl-induced acute lymphoblastic leukemia

Abstract: Arf tumor suppressor ͉ Gleevec ͉ IL-7 ͉ JAK kinases ͉ drug resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(213 citation statements)
references
References 35 publications
6
206
1
Order By: Relevance
“…Alternatively, the discrepancy may derive from differences in the cellular stress-response mechanisms elicited by cytotoxic agents versus targeted agents. In keeping with this latter explanation, the antileukemic response associated with targeted BCR-ABL inhibition is profoundly limited by p19 Arf deficiency in a mouse model (49). Likewise, p53 deficiency imparts resistance to targeted therapy in the context of BCR-ABLinduced leukemias (50), and our results imply that this resistance may stem from p19 Arf /p53 pathway compromise alone, without a need for additional perturbations in p16 Ink4a function.…”
Section: Discussionsupporting
confidence: 54%
“…Alternatively, the discrepancy may derive from differences in the cellular stress-response mechanisms elicited by cytotoxic agents versus targeted agents. In keeping with this latter explanation, the antileukemic response associated with targeted BCR-ABL inhibition is profoundly limited by p19 Arf deficiency in a mouse model (49). Likewise, p53 deficiency imparts resistance to targeted therapy in the context of BCR-ABLinduced leukemias (50), and our results imply that this resistance may stem from p19 Arf /p53 pathway compromise alone, without a need for additional perturbations in p16 Ink4a function.…”
Section: Discussionsupporting
confidence: 54%
“…Introduction of these cells into healthy immunocompetent, syngeneic recipient host animals (hereafter "recipients") generates a fulminant ALL that quickly kills the mice. In direct contrast to the retarded leukemogenic potential of p185 + ;Arf +/+ cells in healthy animals, as few as 20 p185 + ;Arf -/-cells are capable of producing a disseminated pre-B-cell ALL in recipients in less than 4 weeks (Williams et al 2006(Williams et al , 2007. Abundant leukemic cells "marked" with green fluorescent protein (GFP) (expressed in tandem with BCR-ABL) can be recovered from all hematopoietic tissues of moribund animals and can be readily phenotyped, quantified, cultured in vitro, and efficiently transplanted serially and at the same limiting dilution into healthy secondary and tertiary recipients.…”
Section: Modeling Ph + All In the Mousementioning
confidence: 93%
“…These include high hyperdiploidy, hypodiploidy, the translocations t(12;21)(p13;q22)[ETV6-RUNX1], t(1;19)(q23;p13.3) [TCF3-PBX1], t(9;22)(q34;q11)[BCR-ABL1] and rearrangement of the MLL gene at 11q23 in B-progenitor ALL, rearrangement of MYC in mature B-cell leukemia/lymphoma, and rearrangement of the TLX1 (HOX11), TLX3 (HOX11L2), LYL1, TAL1 and MLL genes in T-ALL. [8][9][10][11][12] These translocations frequently involve transcriptional regulators of hematopoiesis and are important initiating events in leukemogenesis, but the observations that these abnormalities are often detectable years before the onset of leukemia and usually do not alone result in leukemia in experimental models 13,14 suggest that cooperating genetic or epigenetic lesions are required. Candidate gene studies have identified lesions such as deletion of the CDKN2A/CDKN2B (encoding the tumor suppressors p16INK4A, p14ARF and p15INK4B) and NOTCH1 in T-ALL, [15][16][17][18] but until recently methods to analyze genetic alterations in a genome-wide fashion have been lacking.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…This is supported by in vivo studies modeling the role of Pax5 haploinsufficiency in leukemogenesis. In a murine retroviral bone marrow transplant model of BCR-ABL1 B-progenitor ALL, 14,69 Pax5 haploinsufficiency increases the penetrance and reduces the latency of B-ALL . 70 Additional CNA of Pax5 and Cdkn2a/b, and sequence mutations of Pax5, were observed in the resulting murine tumors, further supporting a role for these alterations in leukemogenesis.…”
Section: Mutations Of Genes Regulating B-lymphoid Development In Allmentioning
confidence: 99%